BPH Procedural Treatment: The Case for Value-Based Pay for Performance. (21st December 2008) - Stovsky, Mark; Jaeger, Irina
Abstract : The concept of "pay for performance" (P4P) applied to the practice of medicine has become a major foundation in current public and private payer reimbursement strategies for both institutional and individual physician providers. "Pay for performance" programs represent a substantial shift from traditional service-based reimbursement to a system of performance-based provider payment using financial incentives to drive improvements in the quality of care. P4P strategies currently embody rudimentary structure and process (as opposed to outcomes ) metrics which set relatively low-performance thresholds. P4P strategies that align reimbursement allocation with "free market" type shifts in cognitive and procedural care using evidence-based data and positive reinforcement are more likely to produce large-scale improvements in quality and cost efficiency with respect to clinical urologic care. This paper reviews current paradigms and, using BPH procedural therapy outcomes, cost, and reimbursement data, makes the case for a fundamental change in perspective to value-based pay for performance as a reimbursement system with the potential to align the interests of patients, physicians, and payers and to improve global clinical outcomes while preserving free choice of clinically efficacious treatments.